Atividade anormal nos músculos mastigatórios em pacientes com diagnóstico de paralisia cerebral. revisão sistemática de estudos observacionais - Beltramin, Rafael Zaratin (2020)
The objective of the systematic review is to assess whether the diagnosis of cerebral palsy (CP) has abnormal activation of the masseter and bilateral temporal muscles during the masticatory cycle. This review follows the recommendations of the Cochrane Manual for Systematic Reviews of Interventions and the PRISMA statement, and was recorded on the PROSPERO platform. A literature search was performed using an electronic search (MEDLINE, Embase, Cochrane Library, LILACS, BBO, Clinicaltrials.gov and WHO / ICTRP) without restriction of data and language. Gray literature was also examined via OpenGrey. Comparative observational studies (cohort, case-control or cross-sectional analytical) were included, which evaluated the analysis of the activation of the masticatory muscles (temporal and masseter) during the masticatory cycle or maximum voluntary contraction (CVM) as the primary outcome, through analysis by electromyography (EMG) and as a secondary quality of life, assessed by validated scales, for example Quality of Life Related to Oral Health (OHRQOL) and maximum mouth opening, assessed for example by goniometry measurements. Two authors independently selected as references retrieved by the search strategy using the Rayyan software and extracted data from the included studies. Any disagreement was resolved by a third author. The risk of bias assessment was performed using a ROBINS-I scale. We calculated the average differences for continuous results and risk ratios for dichotomous results (95% CI). The electromyographic parameters were combined in meta-analysis using the random effect model in the Review Manager 5.4.1 software. Five cross-sectional studies were included, which analyzed maximum voluntary contraction, masticatory cycle, maximum bite pressure and mouth opening. Abnormal masseter and temporal muscle activity was proven in individuals diagnosed with cerebral palsy.